Emulsifiers in ultra-processed foods in the UK food supply - Alicia Sandall; Leanne Smith; Erika Svensen; Kevin Whelan (Cambridge University Press, 2023)
Abstract Objective: Ultra-processed foods (UPF), including those containing food additive emulsifiers, have received research attention due to evidence implicating them in the pathogenesis of certain diseases. The aims of this research were to develop a large-scale, brand-level database of UPF in the UK food supply and to characterise the occurrence and co-occurrence of food additive emulsifiers. Design: A database was compiled sampling all products from the food categories contributing to energy intake from UPF in the UK from the National Diet and Nutrition Survey (2008-2014). Every food in these categories were identified from online supermarket provision from the 'big four' supermarkets that dominate the market share in the UK, comprising Tesco, Sainsbury's, Asda and Morrisons. Setting: Major supermarkets in the UK. Results: A total of 32 719 food products in the UK supermarket food supply were returned in searches. Of these, 12 844 products were eligible and manually reviewed for the presence of emulsifiers. Emulsifiers were present in 6642 (51·7 %) food products. Emulsifiers were contained in 95·0 % of 'Pastries, buns and cakes', 81·9 % of 'Milk-based drinks', 81·0 % of 'Industrial desserts' and 77·5 % of 'Confectionary'. Fifty-one per cent of all emulsifier-containing foods contained multiple emulsifiers. Across emulsifier-containing foods, there were a median of two emulsifiers (IQR 2) per product. The five most common emulsifiers were lecithin (23·4 % of all products), mono- and diglycerides of fatty acids (14·5 %), diphosphates (11·6 %), and xanthan gum and pectin (8·0 %). Conclusions: Findings from this study are the first to demonstrate the widespread occurrence and co-occurrence of emulsifiers in UPF in the UK food supply.